The haematological profile of female bronze turkeys (Meleagris gallopavo) vaccinated with various commercial strains of Newcastle disease - Schmidt, Elizabeth Moreira dos Santos [UNESP]; Santos, Ivan Felismino Charas; Paulillo, Antonio Carlos [UNESP]; Martins, Gislaine Regina Vieira [UNESP]; Denadai, Janine [UNESP]; Lapela, Ivan Moura [UNESP] (Aosis Open Journals, 2014)
The effects of vaccination on avian blood parameters are poorly understood. The present study was designed to evaluate whether different strains (Ulster 2C, B1, live LaSota and inactivated LaSota) of Newcastle disease vaccines had an effect on the haematological profile of female turkeys. Seventy-five female turkeys were allocated to treatment groups according to vaccination strain. All the birds, except those in the control group, were vaccinated at 32 weeks of age and revaccinated at 40 and 48 weeks of age. Blood samples were obtained for haematological analyses and serum samples for the haemagglutination inhibition test. Haemoglobin concentration was significantly lower (p < 0.05) in vaccinated female turkeys than in the control birds 28 days after vaccination. Monocytes were significantly higher (p < 0.05) in 44-week-old female turkeys vaccinated with inactivated LaSota strain compared with the other groups. Turkeys vaccinated with the B1 strain showed significantly higher (p < 0.05) total white blood cell counts compared with the other groups vaccinated with various commercial strains of the Newcastle disease virus. In conclusion, female turkeys showed significant differences in haemoglobin concentrations, monocytes and white blood cell counts when vaccinated against Newcastle disease.